Short-Term Problems and Long-Term Oriented Policy: EU Cohesion Policy Responding to Crisis - Dominika Wojtowicz; Agnieszka Olechnicka (Barometr Regionalny)
European Union Cohesion Policy (CP ) creates the basis for long-term sustainable development and provides a very significant financial resource in many EU countries. In many disadvantaged regions CP funds have became a main tool supporting implementation of regional development policy. Binding regional policy with long-term CP goals limits however the flexibility of regions in taking measures that go beyond those approved by European Commission within operational programs. In consequence, it can prevent regional authorities from adequate reaction to challenges occurring in the short-term perspective. This paper focuses on the role of CP in responding to short-term problems such as those resulting from the latest financial and economic crisis. The hypothesis on whether the CP management and implementation systems of Regional Operational Programs (ROPs ) remain unchanged in face of short-term disturbances is verified. Our study confirmed the predominantly long-term orientation of CP, as the deterioration of the economic situation in two studied regions did not bring any significant changes related to the main goals, objectives or funds allocation. However, the two case studies proved that regions undertook special actions and implemented projects focused on resolving short-term problems and challenges in the 2007–2013 period.